UPAYA PEMENUHAN GIZI BERDASARKAN KEBIASAAN SARAPAN PADA ANAK USIA SEKOLAH DALAM KELUARGA, DI DESA RANCAWIRU KABUPATEN TEGAL - Dwi Budi Prastiani; Astuti Yuni Nursasi; Widyatuti - (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
Breakfast is an important activity for school-age children before making daily activities. Thisstudy aims to determine the relationship of nutrition fulfillment with breakfast habits of school age children in the family. The descriptive design with crosssectional correlation performedon families with school-age children. Result showed there is statistically significant associationbetween nutrition fulfillment with breakfast habits (p value <α). These efforts include providingfood, giving motivation, feelings of love and role models. The most dominant factor is rolemodel. Health education on the importance of nutrition in school-age children needs to be doneas promotion and prevention intervention.Key words : Breakfast habits, school-age children, family, nutrition fulfillment.